Seven-year follow-up of spontaneous bone regeneration following segmental mandibulectomy: Alternative option for mandibular reconstruction - Mesgarzadeh, Ali Hossein (Dent Res J (Isfahan), 2019)
Bone formation in small deposits following the loss of part of the mandible has often been reported in the literature, but the long-term follow-up reports of bone regeneration extending over the mandible are rare. Even rarer, are reports on the behavior of such new bone in terms of facial development, over a long period and the effect of load on it. A unique case of bone regeneration after resection of a large portion of the mandible in a 9-year-old male patient with myxofibrosarcoma in the body of the mandible is presented here. Intermaxillary fixation and insertion of reconstruction plate after resection without continuity defect were employed. Spontaneous bone regeneration was noted 8 weeks after surgery, and the resected portion of the mandible was regenerated when the patient was seen again 7 years later. Mandibular growth was not significantly affected and almost 7 years after his treatment, without relapsing of pathologic condition, the shape of the mandible is satisfactory without any evidence of bone resorption.